2005
DOI: 10.1158/0008-5472.can-04-1952
|View full text |Cite
|
Sign up to set email alerts
|

The E7 Protein of Cutaneous Human Papillomavirus Type 8 Causes Invasion of Human Keratinocytes into the Dermis in Organotypic Cultures of Skin

Abstract: Human papillomaviruses (HPV) have been implicated in the development of nonmelanoma skin cancer (NMSC). The molecular mechanisms by which these viruses contribute towards NMSC are poorly understood. We have used an in vitro skin-equivalent model generated by transducing primary adult human epidermal keratinocytes with retroviruses expressing HPV genes to investigate the mechanisms of viral transformation. In this model, keratinocytes expressing HPV genes are seeded onto a mesenchyme composed of deepidermalized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
78
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 90 publications
(85 citation statements)
references
References 35 publications
(28 reference statements)
5
78
0
2
Order By: Relevance
“…• C. Organotypic cultures were essentially prepared on de-epidermalized dermis as previously described [46]. Briefly, the reticular dermal surface was repopulated with human fibroblasts and keratinocytes were seeded on the papillary dermal surface and allowed to form a confluent monolayer.…”
Section: Methodsmentioning
confidence: 99%
“…• C. Organotypic cultures were essentially prepared on de-epidermalized dermis as previously described [46]. Briefly, the reticular dermal surface was repopulated with human fibroblasts and keratinocytes were seeded on the papillary dermal surface and allowed to form a confluent monolayer.…”
Section: Methodsmentioning
confidence: 99%
“…The beta HPV types were first isolated in skin cancer-prone patients suffering from a rare autosomal recessive genetic disorder called epidermodysplasia verruciformis, but it is now clear that they are commonly found in the skin of healthy individuals (Pfister, 2003). Characterization of the biological properties of the products of the early genes E6 and E7 from different beta HPV types in in vitro and in vivo model has highlighted the potential carcinogenicity of these viruses (Jackson et al, 2000;Caldeira et al, 2003;Akgul et al, 2005;Dong et al, 2005;Schaper et al, 2005;Accardi et al, 2006;Michel et al, 2006). We showed that expression of E6 and E7 from the beta HPV38 in primary human keratinocytes results in inactivation of the tumour suppressor p53 and pRb and immortalization (Caldeira et al, 2003;Accardi et al, 2006).…”
mentioning
confidence: 99%
“…Independent oncogenic effects may be expected from E6-MAML1 interactions, which repress the Notch signaling pathway, which has tumor suppressor function in the skin (12). HPV8 E7-induced upregulation of the MT1 matrix metalloproteinase may explain invasion of E7-positive keratinocytes into the dermis of organotypic keratinocyte cultures (13).…”
Section: Introductionmentioning
confidence: 99%